Gender Differences in Pathways to Delinquency: the Impact of Family Relationships and AdolescentDepression - Herrera, Veronica (Journal of developmental and life-course criminology, 2017)
The current study examined gender differences in pathways bridging childhood exposure to family violence, adolescent family relationships, adolescent depression, and juvenile delinquency.